Free money for graduate school - Blum, Laurie (H. Holt and Co., 1993)
"There is an enormous amount of money available in direct grants to fund advanced degrees; the trick is to identify the sources of private money and to find the right grant for you. In Free Money for Graduate School, Laurie Blum shows you where and how to apply for the millions of dollars available each year to help finance education costs, including study and research abroad."--BOOK JACKET. "Free Money for Graduate School is a completely revised and updated guide to the more than 1,000 grants and scholarships available for graduate-level study. Arranged alphabetically by subject, the book provides entries detailing all the information you need to apply for free money, including: name, address, phone number, amount of award, restrictions, and deadline for application."--BOOK JACKET.